2013
DOI: 10.1111/j.1744-1609.2012.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Nursing inter-shift handover process in mental health settings: a best practice implementation project

Abstract: This project had shown that handover sessions can be made effective by translating evidence into practice through ongoing evidence-based audit. Continuous evidence-based evaluation, identification and implementation of nursing inter-shift handover process are imperative to enhance patient safety and service delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 9 publications
0
17
0
Order By: Relevance
“…Additionally, coherent intersectoral care must be based on a recovery-oriented approach [ 10 , 11 ]. There are only a few studies that focus on coherent intersectoral care in a psychiatric context [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. These studies highlight issues concerning inadequate communication and coordination across the professional services [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, coherent intersectoral care must be based on a recovery-oriented approach [ 10 , 11 ]. There are only a few studies that focus on coherent intersectoral care in a psychiatric context [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. These studies highlight issues concerning inadequate communication and coordination across the professional services [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The practice is still based on a biomedical model of healing, the The labor market increasingly requires professionals able to meet the demands in the context of care integrality and coordination. Therefore, it is essential that nurses undergo updates and training (permanent and continuing education) that complement their training to offer quality assistance, subsidized in evidence-based practice (24) .…”
Section: Discussionmentioning
confidence: 99%
“…As for the demand for training for nursing professionals, 90% of those surveyed indicated that they needed more training in order to carry out their professional activities. In fact, there are studies which show that more training improves the quality of patient care and reduces adverse effects ( 13 - 14 ) .…”
Section: Discussionmentioning
confidence: 99%